Implementasi Restorative Justice Sebagai Alternatif Pemidanaan Dalam Sistem Peradilan Pidana Untuk Menangani Fenomena Over Kapasitas Di Rutan Berdasarkan Teori Efektivitas Hukum pada Rumah Tahanan Negara Kelas I Labuhan Deli - Thimoty Dwi Felix Barus; Johannes Mangpaul Turnip (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the application of restorative justice as an alternative to punishment in the Class I Labuhan Deli Detention Center and assess its effectiveness in addressing overcrowding in detention centers. The research method used is an empirical approach with data collection through interviews, document studies, and direct observation. The results show that in the 2024–2025 period, there were at least ten criminal cases, such as theft, receiving stolen goods, embezzlement, assault, domestic violence, and plantation violations, which were successfully resolved through restorative justice mechanisms. These resolutions emphasized the restoration of victims' losses, social reconciliation, and reducing the burden of overcrowding inmates. Analysis based on Soerjono Soekanto's theory of legal effectiveness shows that the implementation of restorative justice in the Labuhan Deli Detention Center is quite effective because it meets the factors of legal substance, law enforcement officers, facilities, society, and culture. However, strengthening technical regulations, increasing the capacity of mediators, and ongoing outreach to the community are still needed so that the implementation of restorative justice is truly optimal in realizing justice that is humane, efficient, and socially just.